Дослідження тирозинпротеїнкіназної активності в клітинах слизової оболонки шлунка за умов розвитку виразки та на ранніх етапах її загоєння - Кузьменко, Л.І.; Богданова, О.В.; Кравченко, О.О.; Остапченко, Л.І.; Прокопова, К.В. (Видавничий дім "Академперіодика" НАН України, 2007)
Protein tyrosine kinase activities in membranes and cytosol of rat stomach mucosa cells under conditions of ulcer development and during early stages (five days) of experimental stress ulcer models healing are investigated. The level of these parameters under omeprazole treatment in therapeutic doses is evaluated. It was established that ulcerative disease forming and healing are accompanied by significant abnormalities of the functioning of tyrosine phosphorylation enzymes in stomach mucosa cells during early stages of ulcer healing. The protein tyrosine kinase activities after stressing remained to be essentially reduced in membranes and cytosol. It is shown that enzymes activities were increased on the 4th and 5$th days immediately after ulceration under conditions of omeprazole treatment.